2013
DOI: 10.3168/jds.2012-6215
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of energy use, greenhouse gas emissions, and process economics of the fluid milk process

Abstract: Energy-savings measures have been implemented in fluid milk plants to lower energy costs and the energy-related carbon dioxide (CO2) emissions. Although these measures have resulted in reductions in steam, electricity, compressed air, and refrigeration use of up to 30%, a benchmarking framework is necessary to examine the implementation of process-specific measures that would lower energy use, costs, and CO2 emissions even further. In this study, using information provided by the dairy industry and equipment v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…The flow sheet diagram of the fluid milk process from Tomasula et al (2013) is shown in Figure 1. It is used as the template for the inclusion and development of models for UHT processing of milk, crossflow MF with or without HTST pasteurization, crossflow MF with partial homogenization followed by HTST pasteurization, and PEF processing.…”
Section: Model Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The flow sheet diagram of the fluid milk process from Tomasula et al (2013) is shown in Figure 1. It is used as the template for the inclusion and development of models for UHT processing of milk, crossflow MF with or without HTST pasteurization, crossflow MF with partial homogenization followed by HTST pasteurization, and PEF processing.…”
Section: Model Developmentmentioning
confidence: 99%
“…The fluid milk process model (FMPM; Tomasula et al, 2013) incorporates HTST pasteurization of milk with equipment specifications and cost data, using the commercial software package SuperPro Designer (http://www.intelligen.com, Version 9.0 Build 8; Intelligem Inc., Scotch Plains, NJ). The flow sheet diagram of the fluid milk process from Tomasula et al (2013) is shown in Figure 1.…”
Section: Model Developmentmentioning
confidence: 99%
See 3 more Smart Citations